PARTIAL FETOTOMY FOR THE DELIVERY OF A SCOLIOTICANKYLOSED FETUS IN A COW - SINGH, NAVDEEP; GHUMAN, S P S; SINGLA, V K; HONPARKHE, M (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to scoliotic-ankylosed fetusin a cow and its vaginal deliverythrough partial fetotomy is reported.